2020
DOI: 10.1186/s41983-019-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-6 in ischemic stroke outcome

Abstract: Background: High levels of inflammatory markers such as C-reactive protein (CRP) and interleukin (IL)-6 are associated with worse outcome after ischemic stroke. Objectives: To study whether the level of IL-6 following ischemic stroke is related to the severity of stroke, infarct volume, stroke subtype, and its impact on stroke outcome. Materials and methods: A total of 90 patients of acute ischemic stroke were enrolled with calculation of infarct volume in MRI brain, and serum IL-6 samples were obtained within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…Meanwhile, increases in inflammatory markers have been shown to reflect ischemic injuries in clinical settings. Cytokines, such as interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α), ficolin-1 and others, have been reported to increase in relations with the incident of stroke [ 7 , 8 , 9 , 10 ]. Therefore, decreasing inflammatory activity may be a goal for effective therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, increases in inflammatory markers have been shown to reflect ischemic injuries in clinical settings. Cytokines, such as interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α), ficolin-1 and others, have been reported to increase in relations with the incident of stroke [ 7 , 8 , 9 , 10 ]. Therefore, decreasing inflammatory activity may be a goal for effective therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, monocyte chemotactic protein-1 (MCP-1), matrix metalloproteinase-9 (MMP-9) and interleukin-6 (IL-6) appear within hours of a stroke, but tissue inhibitor of matrix metalloproteinase-1 (TIMP-1), C-reactive protein (CRP), and S100B appear after 12-24 hours and each biomarker had differing abilities to predict 90-day outcomes of stroke [37]. More recently, IL-6 levels correlated with the severity of stroke at admission based on the NIHSS and mRS and also predicted recurrence of stroke [38]. The Reasons for Geographic and Racial Differences in Stroke (REGARDS) study enrolled 30,237 participants and showed that IL-6, but not IL-8 or IL-10 was strongly associated with risk of incident stroke over 5.4 years [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IL-17, IL-1β also induces the blood level of IL-6. Plasma IL-6 is widely studied as a strong predictor of ischemic stroke outcome [ 66 ]. Significant elevation in plasma, as well as brain tissue concentration of IL-6 or mRNA have been described in either clinical or experimental studies about ischemic stroke and transient ischemic attacks [ 67 - 69 ].…”
Section: Covid-19 Nets and Ischemic Stroke: A Postulated Linkmentioning
confidence: 99%